Effects of pollen enriched diet on hypopharyngeal glands’ morphology and morphometry and vitellogenin transcription levels in honey bees - Claudia D’Emilio; Viviana Valenzano; Paola Maiolino; Karen Power; Manuela Martano; Gennaro Di Prisco (Italian Journal of Animal Science)
Pollen proteins are necessary for the development of the hypopharyngeal glands (HPGs), and for Vitellogenin (VG) synthesis, responsible for producing royal jelly, essential for larval development and queen feeding. This study aims to evaluate morphological aspects and morphometrical parameters of HPGs, and VG transcription levels in caged honey bee workers fed with differential diets. Morphological and morphometrical analysis was performed on Haematoxylin and Eosin (HE) stained honey bee samples, while qRT-PCR evaluated VG transcription levels. Histologically honey bees fed with a diet based on sucrose and multifloral pollen patty (Diet B) showed more developed and functioning HPGs acini than honey bees fed a diet based only on sucrose patty (Diet A). Morphometric results confirmed that HPG size increased in honey bees fed with Diet B. The relative transcriptional level of VG showed that it varied significantly over time but was independent of the tested diets. Our results confirm that a diet rich in pollen is necessary for the normal development and function of HPGs and that the amount of secretion is positively correlated with glandular activity and acinar size. Therefore, using integrated diets with pollen could be a useful strategy to improve honey bee health and productivity.